European Schemes of Social Assistance: An Empirical Analysis of Set-Ups and Distributive Impacts - Katja Hölsch; Margit Kraus (Luxembourg Income Study (LIS), 2002)
This paper analyses the distributive impacts of various regulatory and institutional settings of European schemes of social assistance. For this purpose, two sets of classifications of European schemes of social assistance are introduced that classify the systems according to regulatory arrangements and degree of centralization, respectively. Subsequently, the distributive impacts of five selected EU systems are calculated on the basis of LIS data and their relationship to class assignment is investigated.
Keywords: 330; Öffentliche Sozialleistungen; Öffentliche Sozialleistungen; Systemvergleich; Wirkungsanalyse; Einkommensverteilung; EU-Staaten